2011
DOI: 10.1177/1350508411429399
|View full text |Cite
|
Sign up to set email alerts
|

The politics of knowledge, epistemological occlusion and Islamic management and organization knowledge

Abstract: This article argues that Islamic management and organization knowledge (MOK) is relatively under- and mis-represented in the literature. This conclusion is reached following a detailed literature survey and analysis which also examines some of the core representational practices used to account for Islam in the literature: the persistence of essentialism and orientalism; the disposition to refract instances of Islamic MOK through Northern lenses; and the tendency for some Southern scholars and institutions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 85 publications
0
27
0
2
Order By: Relevance
“…This is not least because such assimilation may well undermine the plurality of global perspectives sought through the invitation. “Those not of the North are obliged to either conform and play the game or not be given entry and voice” (Ul-Haq & Westwood, 2012, p. 243). This challenge is also highlighted by authors well-established in the mainstream: “Given the worldwide dominance of U.S. journals, researchers from other countries seeking publications in these journals often have to adopt similar epistemological and ontological views to that of much U.S. scholarship—overlooking the idiosyncratic qualities of their own research contexts” (Bruton, Zahra, & Cai, 2018, p. 352).…”
Section: Against Becoming Coloniesmentioning
confidence: 99%
“…This is not least because such assimilation may well undermine the plurality of global perspectives sought through the invitation. “Those not of the North are obliged to either conform and play the game or not be given entry and voice” (Ul-Haq & Westwood, 2012, p. 243). This challenge is also highlighted by authors well-established in the mainstream: “Given the worldwide dominance of U.S. journals, researchers from other countries seeking publications in these journals often have to adopt similar epistemological and ontological views to that of much U.S. scholarship—overlooking the idiosyncratic qualities of their own research contexts” (Bruton, Zahra, & Cai, 2018, p. 352).…”
Section: Against Becoming Coloniesmentioning
confidence: 99%
“…The coloniality of knowledge refers to the intellectual hegemony of Western knowledge production and dissemination, which attained and sustained dominance through participation in colonisation, and the persistent intellectual and cultural imperialism that has marginalised and, in some cases, eradicated alternative knowledge systems and ways of working and organising (Alcadipani and Faria, 2014; Calás and Smircich, 2003; Ibarra-Colado, 2006; Jack et al, 2011; Mignolo, 2007; Misoczky, 2011; Quijano, 2007; Said, 1978; Spivak, 1988; Ul-Haq and Westwood, 2012; Walsh, 2007). Decolonial theorists maintain that modernity and the coloniality of knowledge enforce Western management discourse and practices upon the lives and experiences of those in the non-West, dictating a Western tradition of managerial thinking that defines how and what should be studied and practised (Imas and Weston, 2012).…”
Section: Becoming a Decolonial Feminist Ethnographermentioning
confidence: 99%
“…Ulluwishewa (1992) observed that Indigenous cultures typically have a variety of types of sub‐knowledge systems; some dealing with natural/physical environment, some with cognitive environment, some with social environment, etc. Within Eurocentric culture, religious knowledge systems and the Science knowledge system are often viewed as distinct entities, whereas Islamic epistemology sees religion and Science more as complementary parts of a continuum (Ul‐Haq and Westwood 2012). It is extremely important to be aware of this intra‐cultural diversity when attempting to engage across knowledge system interfaces (Moller et al 2009 a , Hanazaki et al 2013, Reo et al 2017).…”
Section: Knowledge System Social Scalementioning
confidence: 99%